Giant magnetoimpedence effects in micro-patterned Co52Fe32B11Si5 amorphous ribbons - Park, Sun Hee; Chun, Dong Won; Han, Jun Hyun; Kim, Young-Ho; Jeung, Won Young (WILEY-V C H VERLAG GMBH, 2007)
We report the giant magnetoimpedence (GMI) effect in Co52Fe32B11Si5 amorphous ribbon micro-patterned using photolithography and wet etching process. The effects of AC frequency and amplitude on GMI characteristics are investigated in our micro-patterned GMI devices. Furthermore, it is shown that thickness of patterned ribbon plays a significant role on the GMI behaviour and response condition of AC frequency and amplitude. (c) 2007 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: MAGNETO-IMPEDANCE; 2ND-HARMONIC AMPLITUDE; MI; DEPENDENCE; SENSOR; WIRE